INTERAKSI EDUKATIF GURU PAI DALAM MEMBANGUN SIKAP KESALEHAN SOSIAL PESERTA DIDIK DI SMP NEGERI 8 KOTA BENGKULU - Hanisah, Umi; Mindani; Latipah, Nurlia (Yayasan Darussalam Bengkulu, 2021)
The background of this research problem is related to PAI learning practices which are still often found only concentrating on cognitive theoretical issues from the growth of Islamic values ​​and ignoring the development of affective and conative-volative aspects, namely the willingness and determination to practice Islamic values. . As a result, there is often a gap between the understanding of religion and its practice in everyday life. There are many religious people who are individually pious but not socially pious. Based on this problem, further research was conducted on the educative interaction of PAI teachers and their implementation on the attitudes of students' social piety. This type of research uses qualitative research with an educational sociology approach. Data collection techniques were carried out through observation, interviews, and documentation. While the research data were analyzed using qualitative analysis, namely data reduction, data presentation, verification, and conclusions. The data validity test in this study is data triangulation, namely technical triangulation, source triangulation, and time triangulation. Based on the results of this study, it shows that: First, the Pattern of Educational Interaction conducted by PAI teachers, namely 1) One-way interaction patterns, this one-way interaction pattern is realized by PAI teachers using the lecture method. 2) The pattern of two-way interaction, for this two-way interaction, is realized by the PAI teacher using the question and answer method. 3) The pattern of interaction is multi-directional, this interaction the PAI teacher manifests in the use of group discussion learning methods and several religious activities related to social piety. Second, the educative interaction of PAI teachers at SMP Negeri 8 Bengkulu City is implemented through the PAI KBM process, namely getting students to pray at the beginning and at the end of learning, giving apperception to previous learning materials, mastering and delivering good learning materials and being able to connect with problems that exist in the community, create a pleasant learning atmosphere with the help of media and learning strategies, be open, inclusive, objective, and non-discriminatory towards students, provide evaluations to measure students' understanding of learning materials. Outside of KBM PAI, namely familiarizing the values ​​of Islamic teachings to students through religious activities in schools.